The world in Brussels, Brussels in the world - Jean-Pierre Hermia; Christian Vandermotten (Brussels Studies, 2015)
“The world in Brussels. Brussels in the world” is the theme of the 2015 edition of the Night of Knowledge on Brussels, on Friday, 27 November at the Kaaitheater. By means of short presentations and discussions, supported by scientific data, the evening will provide the opportunity to obtain information on and to debate about the different aspects of the internationalisation of the Region: insertion within advanced service networks, the informal economy, educational segregation, juvenile delinquency, contemporary art or the role of universities in welcoming refugees.Prior to this moment of exchange and reflection, Brussels Studies is publishing in its number 94, a short note in which Jean-Pierre Hermia (Brussels Institute for Statistics and Analysis) and Christian Vandermotten (Université Libre de Bruxelles) review two key factors: the characteristics of the presence of foreigners in the region and the place and the specificity of Brussels in relation to other major European cities.